Effects of Supplemental Feeding on Home Range Size and Survival of Northern Bobwhites in South Georgia - D. Clay Sisson; H. Lee Stribling; Dan W. Speake (National Quail Symposium Proceedings, 2017)
We studied the effects of supplemental feeding on fall-spring covey home range size and survival of radio-marked northern bobwhites (Colinus virginianus) for 3 years in southwest Georgia. A total of 372 radio-marked bobwhites were monitored on 2 separate study areas for 25 weeks from fall-spring each year from November 1993 through May 1996. The traditional supplemental feeding program of bi-weekly broadcast spreading of whole grains from November through May was discontinued on one of the study areas during 1993-1994 and 1994-1995. Supplemental feed was distributed on both areas during fall-spring 1995-1996. During the 2 years of no feeding, fall-spring covey home ranges were larger (P = 0.04) on the unfed study area. During the first of these 2 years (1993-1994), fall-spring survival of birds without supplemental feed (S = 0.127) was lower (P = 0.005) than that of fed birds (S = 0.432). During the 1994-1995 season while covey home ranges of birds without supplemental feed were still slightly larger (P = 0.04), there was no difference (P = 0.76) in survival between bobwhites on the sites with and without supplemental feed. Coveys seen per hour hunted was significantly lower (P = 0.007) on the treatment (unfed) area during 2 years. During the year supplemental feed was distributed on both sites, there was no difference in home range size (P = 0.87), survival (P = 0.90), or hunting success (P = 0.82) between the 2 study sites. Supplemental feeding may reduce bobwhite movements and home range size thereby enhancing survival because of less exposure to predation. However, such an effect will probably vary among years in relation to prevailing weather and native vegetation conditions. The specific mechanisms through which supplemental feeding may effect bobwhite population performance remain unknown and require additional study.